Cybersecurity policies and strategies for cyberwarfare prevention - Richet, Jean-Loup, 1988- (Hershey, PA : Information Science Reference, 2015)
'This book serves as an integral publication on the latest legal and defensive measures being implemented to protect individuals, as well as organizations, from cyber threats by examining online criminal networks and threats in both the public and private spheres'--
Includes bibliographical references (pages 397-461) and index.
Keywords: Cyberterrorism -- Prevention; Cyber intelligence (Computer security).; Cyberspace operations (Military science).; Computer crimes -- Prevention